2022
DOI: 10.3389/fcvm.2022.1033457
|View full text |Cite
|
Sign up to set email alerts
|

PERM1 regulates energy metabolism in the heart via ERRα/PGC−1α axis

Abstract: AimsPERM1 is a striated muscle-specific regulator of mitochondrial bioenergetics. We previously demonstrated that PERM1 is downregulated in the failing heart and that PERM1 positively regulates metabolic genes known as targets of the transcription factor ERRα and its coactivator PGC-1α in cultured cardiomyocytes. The aims of this study were to determine the effect of loss of PERM1 on cardiac function and energetics using newly generated Perm1-knockout (Perm1–/–) mice and to investigate the molecular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…As a disordered protein, Perm1 lacks conventional structure and is likely controlled by differential posttranslational modifications. Other partners for Perm1 in the heart include transcription co-activators BAG6, Kank2, ERRα and PGC-1α ( Oka et al, 2022 ); among these we identified Kank2 as lamin A/C-associated (and unaffected by IL10-KO) in the heart.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As a disordered protein, Perm1 lacks conventional structure and is likely controlled by differential posttranslational modifications. Other partners for Perm1 in the heart include transcription co-activators BAG6, Kank2, ERRα and PGC-1α ( Oka et al, 2022 ); among these we identified Kank2 as lamin A/C-associated (and unaffected by IL10-KO) in the heart.…”
Section: Discussionmentioning
confidence: 83%
“…Transcription co-activator Perm1, an essential regulator of mitochondrial and cardiac energetics ( Oka et al, 2022 ) and fatty acid metabolism ( Huang et al, 2022 ), was lamin A/C-associated in hearts and recognized by mature lamin A in the peptide array. Perm1 is attractive to consider in the context of frailty because it also regulates genes required for endurance exercise and promotes mitochondrial biogenesis and oxidative capacity in muscle ( Cho et al, 2016 ; Cho et al, 2019 ; Cho et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is limited understanding of the role of the ATF6B protein, however it appears to protect neurons (30) and pancreatic beta cells (31) from endoplasmic reticulum stress-induced cell death, albeit the relative levels of ATF6A and ATF6B could be more important that levels of ATF6B alone (32). BAG6 (also called BAT3) is located within the HLA class III gene cluster and is implicated in many functions (reviewed in (33)) including apoptosis (34), removal of mitochondria (35) and neurodegeneration-associated protein aggregates (36), modulating immune (37) and anti-viral response (38), de ning dendritic cell functions (39) and energy switching in cardiomyocytes (40). BAG6 is also required for glucose uptake by adipose and muscle tissues, via regulation of SLC2A4 (or GLUT4) translocation to the cell surface (41) and alternative splicing of BAG6 has been observed in an obesity and/or glycaemic control-dependent manner (42).…”
Section: Discussionmentioning
confidence: 99%
“…PERM1 expression levels increase during normal murine cardiomyocyte development and are conversely reduced in the human ailing heart, and its overexpression in murine neonatal cardiomyocytes increases the mitochondrial number, respiration, oxidative metabolism, and resistance to hypoxia/reoxygenation [75]. PERM1 physically interacts with both PGC-1α and ERRα and PERM1 KO mice show profound contractile, metabolic, and energy metabolism shortcomings [76]. These results suggest that pharmacologic activation of the PGC-1α/ERRα/PERM1 axis could improve cardiac function in different pathological conditions of the heart, including contractile dysfunctions caused by chronic heart diseases, mitochondrial dysfunction induced by doxorubicin therapy and hypoxia/reoxygenation-derived injury.…”
Section: Heartmentioning
confidence: 99%